Role of the English language in the Ghanaian hospitality industry: perceptions of hospitality students of a selected technical university - Ramos Asafo-Adjei; Frances Betty Fraikue; Elvis ResCue (Discover Education)
Abstract The role of the English language in the Ghanaian hospitality industry was explored in this study. Specifically, the research question addressed is: what is the role of the English language in the Ghanaian hospitality industry? Using the quantitative descriptive survey research design, a questionnaire survey was carried out among all first year Hospitality Management Bachelor of Technology students (n = 125) of the Takoradi Technical University. The data was analysed using expressive statistics (frequencies and percentages) and Pearson’s correlation. The Service Quality Gap Model (Zeithaml and Bitner in Service marketing: integrating customer focus across the firm, 2nd edn, Irwin McGraw-Hill, New York, 2003) was adapted for this study. Results revealed that the English language is crucial to the Ghanaian hospitality industry and that the basic English language skills (speaking, listening, reading and writing) were central to hospitality operations in Ghana. Lecturers, curriculum developers and key players in the hospitality industry should team up to identify specific language weaknesses which students exhibit in order to address them through properly planned curriculum and andragogical practices.